2012
DOI: 10.1016/j.gynor.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine carcinoma of the cervix during pregnancy: A case report

Abstract: ► Neuroendocrine carcinoma of the cervix is a rare and aggressive malignancy. ► A multimodality approach must be individualized when diagnosed during pregnancy. ► We report the use of a therapeutic cervical cone and adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…It is as low as 0.31–3% according to literature [1, 2]. Until now 18 cases were reported about small cell neuroendocrine cervical cancer that occurred during pregnancy [318]. Table 1 lists the features of all the 18 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is as low as 0.31–3% according to literature [1, 2]. Until now 18 cases were reported about small cell neuroendocrine cervical cancer that occurred during pregnancy [318]. Table 1 lists the features of all the 18 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Her first-order cousin had cervical cancer at age 22, and the maternal grandmother died of cervical cancer [14]. The youngest gestational age was just 10 weeks and the patient remained adamant about preserving the pregnancy; then she had neoadjuvant chemotherapy (NACT) of 4 cycles and delivered at 36 weeks [3]. Only one newborn out of eighteen was dead on day 27 of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…Nine of the 10 patients diagnosed after 25 weeks’ gestational age underwent elective cesarean section followed by a radical hysterectomy or chemotherapy. Teefey et al 7 reported a case of SCCC during pregnancy diagnosed at 10 weeks’ gestation, and they performed neoadjuvant chemotherapy with etoposide and cisplatin (EP/PE) because the patient declined a radical hysterectomy. In the present case, we initially performed a radical hysterectomy considering the gestational age at diagnosis and the estimated 10% 5-year survival rate which we calculated from the 10 above-mentioned cases.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of a radical hysterectomy for SCCC during pregnancy. Since 1990, 10 cases of SCCC during pregnancy [5][6][7] were reported in the English literature (Table 1). The initial treatment option depended on whether or not the fetus had extrauterine survival potential.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown small cell carcinoma of the uterine cervix to represent fewer than 2% of all invasive cervical cancers [ 8 , 9 ]. Some small series and individual case reports of patients with cervical small cell carcinoma are known in the literature; however, only very rare reports of this disease being initially diagnosed in gravid cervices are known [ 10 13 ]. Establishing a definitive diagnosis of this aggressive malignancy by cervicovaginal cytology testing alone can be especially challenging, as ancillary studies (such as immunocytochemistry) are commonly employed in confirming a specific diagnosis [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%